Dealing With Discrimination On Crazy Rich Asians Movie - Nurmalia, Lia; Yastanti, Unpris; Adi, Wiruma Titian; Rohati, Titi Dewi (UNIVERSITAS PAKUAN, 2024)
The purpose of this research are to figure out (1) the effects of discrimination and (2) how to deal with discrimination to finally give the discriminated person some positive effects. This research is arranged by using descriptive qualitative method. The data was taken from Crazy Rich Asians movie by selecting the scene of discrimination cases and grouping them into some types of discrimination. The fundamental theory used in analyzing this research is from Stafrace. The results show there are four types of negative effects experienced by the main character, they are marginalization, disempowerment, low self-esteem and self-identity, and negative behaviours. While in dealing with discrimination, the main character of the movie focus on 4 ways, (1) focus on her strength, (2) seek support system, (3) help herself think clearly, and (4) don’t dwell. Finally, in the way of her ability in handling the discrimination, she found three positive effects after being treated. She becomes more courageous, though, and more confident